Multimodal diaphragmatic ultrasound indicators in healthy adults: reliability and consistency observation by ultrasound physician and critical care physician - Haotian Zhao; Ling Long; Yi Liu; Yaru Yan; Xiaona Wang; Heling Zhao; Li Li (Frontiers in Medicine)
BackgroundThis study aimed to establish normal reference values for multimodal diaphragmatic ultrasound indices in healthy adult volunteers and evaluate intra-and inter-observer consistency between ultrasound physicians and critical care physicians.MethodsAn ultrasound physician (US physician) used techniques such as B-mode, M-mode, Tissue Doppler Imaging (TDI), and shear wave elastography (SWE) to measure diaphragmatic parameters in 46 healthy adults during quiet and deep breathing. A critical care physician (CC physician) trained in diaphragmatic ultrasound repeated these measurements. Consistency was analyzed in intra-researcher and inter-researchers of various diaphragmatic ultrasound indicators.ResultsDiaphragm thickness at the end of expiration, end of inspiration, and end of deep inspiration (DT-ee, DT-ei, and DT-edi) in both B-mode and M-mode method of males were higher than that of females, Diaphragm shear modulus-edi of males is higher than that of females (P<0.05). Between different diaphragmatic ultrasound indicators, the study showed a moderate consistency of peak contraction velocity (PCV) and peak relaxation velocity (PRV) in intra-researcher of CC physician and inter-researchers between US physician and CC physician, (ICC = 0.678 and 0.704, P < 0.001). For other multiple diaphragm ultrasound indicators, our study showed an excellent consistency in both intra-researcher and inter-researchers (ICC = 0.824–0.994, P < 0.001). For DT measurement by B-mode and M-mode, it showed an excellent consistency in both intra-researcher, intra-researcher of US physician, intra-researcher of CC physician and total cases (ICC = 0.919–0.960, P < 0.001). Correlation analysis showed a moderate positive correlation between diaphragm displacement during quiet breathing (DD-qb) and pleural sliding displacement (PSD) in US physician (r = 0.568), CC physician (r = 0.470), and total cases (r = 0.511), with significant differences (P < 0.05).ConclusionUltrasound-based assessment of diaphragmatic function is a reliable method. This study provides normal reference values and highlights the high observer reproducibility among experienced ultrasound and critical care physicians.